2021
DOI: 10.21817/indjcse/2021/v12i3/211203207
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ambiguity of Noun Using Multimodal Approach

Abstract: It is truly amazing that human beings can easily understand and comprehend the intended meaning of an ambiguous word. The meaning of an ambiguous word differs with its usage in a different context. Still, human beings can Fig. out the meanings with ease. We have machine translation (MT) systems that can translate from a source language to its equivalent target language. The main intension of these MT systems is to seamlessly transfer the intended meaning of the source text to its target text. But due to ambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The study also discovered that the most important factor determining MRR was cutting speed, whereas the most important factor affecting surface roughness was feed rate. [12] The goal of the study was to utilise the Taguchi technique and grey relational analysis to optimize the milling settings for AISI 304 austenitic stainless steel. The research revealed that a cutting speed of 100 m/min, a feed rate of 0.15 mm/rev, and a depth of cut of 0.2 mm were the ideal machining settings for producing the maximum MRR and the lowest surface roughness.…”
mentioning
confidence: 99%
“…The study also discovered that the most important factor determining MRR was cutting speed, whereas the most important factor affecting surface roughness was feed rate. [12] The goal of the study was to utilise the Taguchi technique and grey relational analysis to optimize the milling settings for AISI 304 austenitic stainless steel. The research revealed that a cutting speed of 100 m/min, a feed rate of 0.15 mm/rev, and a depth of cut of 0.2 mm were the ideal machining settings for producing the maximum MRR and the lowest surface roughness.…”
mentioning
confidence: 99%